Zintegrowane zarządzanie logistyczne dystrybucją w przedsiębiorstwach branży BHP - Dyczkowska, Joanna (The Integration Logistic Management of Distribution in Firms From the Branch of Safety and Hygiene of Work, 2008)
The paper presents logistic conception and the influence on the progress of firms from the branch of safety and hygiene of work, the connection between supplier, customer and forwarder. The quality system train to a firm (for example Polstar and Grene) lets arrange the distribution process. One of the quality processes is the logistic customer service, which is very important in the logistic chain.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 264-272